Catalyst and method for producing the same
Patent Information
- Application Number
- JP2023132548
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-02-28
AI Technical Summary
【0015】 本発明によれば、高い触媒活性を有する触媒及びその製造方法を提供することができる。
Smart Images

Figure 2025027619000001 
Figure 2025027619000002 
Figure 2025027619000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a catalyst and a method for producing the same. [Background technology]
[0002] Applications of gold particle-supported catalysts, in which gold particles are supported on the surface of a carrier such as an oxide, are being considered. Applications of the catalysts are being considered for indoor air purification such as carbon monoxide oxidation removal, atmospheric environmental conservation such as NOx reduction, fuel cell-related reactions such as selective oxidation of carbon monoxide in hydrogen, and chemical process reactions such as propylene oxide synthesis reaction from propylene.
[0003] For example, Patent Document 1 discloses a gold particle support obtained by adding a gold hydroxo anion complex solution to SiO2 support powder, evaporating the water, and then baking at 350°C. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2008-259993 A Summary of the Invention [Problem to be solved by the invention]
[0005] In gold particle supports, not only the gold particles but also the oxide support can contribute to the catalytic activity. However, since the activity of SiO2 supports is low, it is difficult to further improve the catalytic activity of gold particle supports.
[0006] The present invention has been made in consideration of the above-mentioned current state of the prior art, and a main object of the present invention is to provide a catalyst having high catalytic activity and a method for producing the same. [Means for solving the problem]
[0007] As a result of intensive research, the present inventors have found that by adjusting the components of the support, catalytic activity equal to or higher than that of a SiO2 support can be obtained. In the following, various aspects of the catalyst and its manufacturing method for solving the above problems will be described.
[0008] The catalyst of the first aspect is characterized in that fine gold particles are supported on a porous glass support containing SiO2 and ZrO2.
[0009] The catalyst of the second embodiment is the same as that of the first embodiment, except that the porous glass support further contains TiO2.
[0010] In the catalyst of embodiment 3, in embodiment 1 or 2, the median of the pore size distribution of the porous glass support is preferably 1 to 1000 nm.
[0011] In the catalyst of embodiment 4, in any one of embodiments 1 to 3, the average particle size of the gold particles is preferably 0.1 to 10 nm.
[0012] The catalyst of the fifth embodiment is preferably a catalyst for purifying exhaust gas in any one of the first to fourth embodiments.
[0013] The method for producing the catalyst of the sixth aspect is a method for producing the catalyst of any one of the first to fifth aspects, and is characterized by comprising a solution preparation step of obtaining a gold complex solution by proceeding with a hydrolysis reaction of the gold compound in a solution of pH 8 or more in which a halogen-free trivalent gold compound is dispersed, in the presence of a conjugate base of a weak acid, and a supporting step of impregnating a porous glass carrier with the gold complex solution to support gold particles on the porous glass carrier.
[0014] In the method for producing a catalyst of the seventh embodiment, in the sixth embodiment, the porous glass support is preferably produced by dissolving one phase of spinodally separated glass with an acid. Effect of the Invention
[0015] According to the present invention, it is possible to provide a catalyst having high catalytic activity and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Preferred embodiments will be described below. However, the following embodiments are merely examples, and the present invention is not limited to the following embodiments.
[0017] <Catalyst> The catalyst of the present invention is characterized in that gold particles are supported on a porous glass carrier containing SiO2 and ZrO2. In other words, the catalyst of the present invention is characterized in that it comprises a porous glass carrier containing SiO2 and ZrO2, and gold particles supported on the porous glass carrier.
[0018] <Porous glass carrier> The carrier used in the present invention is made of porous glass containing SiO2 and ZrO2. A carrier having this composition (porous glass carrier) has excellent alkali resistance and acid resistance, and also has excellent catalytic activity. The components of the porous glass carrier are described below. In the description of the component contents of the porous glass carrier, "%" means "mass %" unless otherwise specified.
[0019] SiO2 is the main component of the network-forming oxide in the porous glass carrier. The lower limit of the SiO2 content is preferably 40% or more, 50% or more, 60% or more, 70% or more, and particularly 80% or more, and the upper limit of the SiO2 content is preferably 99% or less, 98% or less, 95% or less, 90% or less, and particularly 89% or less. If the SiO2 content is too low, the weather resistance and mechanical strength of the porous glass carrier tend to decrease. If the SiO2 content is too high, it will hinder the introduction of other components.
[0020] ZrO2 is a component that enhances the alkali resistance of the porous glass carrier. It is also a component that enhances catalytic activity. The lower limit of the ZrO2 content is preferably 1% or more, 2% or more, and particularly 5% or more, and the upper limit of the ZrO2 content is preferably 50% or less, 40% or less, 30% or less, 25% or less, and particularly 20% or less. If the ZrO2 content is too low, the above effects cannot be obtained. If the ZrO2 content is too high, the mechanical strength of the porous glass is weakened.
[0021] The lower limit of the SiO2+ZrO2 content (the total amount of SiO2 and ZrO2) is preferably 41% or more, 50% or more, 60% or more, 70% or more, 80% or more, and particularly preferably 90% or more. If the SiO2+ZrO2 content is too low, it becomes difficult to obtain the above effects. From the viewpoint of introducing other components, the upper limit of the SiO2+ZrO2 content may be 99.9% or less, 99% or less, 98% or less, and particularly preferably 95% or less.
[0022] The porous glass carrier preferably further contains TiO2. The inclusion of TiO2 can further increase the catalytic activity. The lower limit of the TiO2 content is preferably 0% or more, 0.1% or more, and particularly 0.5% or more, and the upper limit of the TiO2 content is preferably 15% or less, 10% or less, 8% or less, and particularly 5% or less. If the TiO2 content is too high, the mechanical strength of the porous glass is weakened.
[0023] From the viewpoint of improving weather resistance and mechanical strength, the porous glass carrier preferably further contains B2O3, Al2O3, CaO, P2O5, Na2O and K2O. More specifically, the lower limit of the content of B2O3+Al2O3+CaO+P2O5+Na2O+K2O (the total amount of B2O3, Al2O3, CaO, P2O5, Na2O and K2O) is preferably 0% or more, particularly 0.1% or more, and the upper limit of the content of B2O3+Al2O3+CaO+P2O5+Na2O+K2O is preferably 15% or less, 10% or less, 8% or less, particularly 5% or less. The preferred ranges of the contents of each of the components B2O3, Al2O3, CaO, P2O5, Na2O and K2O are as follows:
[0024] B2O3 is a component that forms a glass network. The lower limit of the B2O3 content may be 0% or more, particularly 0.1% or more. On the other hand, from the viewpoint of improving the weather resistance of the porous glass carrier, the upper limit of the B2O3 content is preferably 15% or less, 10% or less, 8% or less, 5% or less, 3% or less, or 1% or less, and particularly preferably substantially not contained. In the present invention, "substantially not contained" means that it is not intentionally contained as a raw material, and objectively refers to a content of less than 0.1%.
[0025] Al2O3 is a component that improves the weather resistance and mechanical strength of the porous glass carrier. The lower limit of the content of Al2O3 is preferably 0% or more, particularly 0.1% or more. On the other hand, from the viewpoint of introducing other components, the upper limit of the content of Al2O3 is preferably 15% or less, 10% or less, 8% or less, 5% or less, particularly 3% or less.
[0026] MgO, CaO, SrO and BaO are components that contribute to improving the alkali resistance of the porous glass carrier. The lower limit of the content of MgO, CaO, SrO and BaO is, for example, 0% or more, particularly 0.1% or more, respectively. On the other hand, from the viewpoint of promoting phase separation, the upper limit of the content of MgO, CaO, SrO and BaO is preferably 15% or less, 10% or less, 8% or less, 5% or less, particularly 3% or less, respectively. In addition, when at least two or more components selected from MgO, CaO, SrO and BaO are contained, the lower limit of the total amount is preferably 0% or more, particularly 0.1% or more, and the upper limit of the total amount is preferably 10% or less, 8% or less, 5% or less, particularly 3% or less. Among MgO, CaO, SrO and BaO, it is particularly preferable to contain CaO, since it has a particularly large effect of improving the alkali resistance of the porous glass carrier.
[0027] P2O5 is a component that contributes to improving the alkali resistance of the porous glass carrier. The lower limit of the P2O5 content is, for example, 0% or more, and particularly preferably 0.1% or more. On the other hand, from the viewpoint of preventing crystallization, the upper limit of the P2O5 content is preferably 15% or less, 10% or less, 8% or less, 5% or less, and particularly preferably 3% or less.
[0028] The lower limit of the Na2O content may be 0% or more, particularly 0.1% or more. On the other hand, from the viewpoint of improving the weather resistance of the porous glass carrier, the upper limit of the Na2O content is preferably 15% or less, 10% or less, 8% or less, 5% or less, 3% or less, particularly 1% or less.
[0029] The lower limit of the K2O content may be 0% or more, particularly 0.1% or more. On the other hand, from the viewpoint of improving the weather resistance of the porous glass carrier, the upper limit of the K2O content is preferably 15% or less, 10% or less, 8% or less, 5% or less, 3% or less, particularly 1% or less.
[0030] In addition to the above components, the porous glass carrier may contain Li2O, ZnO, La2O3, Ta2O5, TeO2, Nb2O5, Gd2O3, Y2O3, Eu2O3, Sb2O3, SnO2, Bi2O3, etc. in an amount of 15% or less, 10% or less, 5% or less, especially 3% or less, or in a total amount of 20% or less.
[0031] In addition, since PbO is an environmentally hazardous substance, it is preferable that it is not substantially contained.
[0032] The median of the pore size distribution of the porous glass carrier is preferably 1000 nm or less, 200 nm or less, 150 nm or less, 120 nm or less, 100 nm or less, 90 nm or less, 80 nm or less, 70 nm or less, 60 nm or less, and particularly preferably 50 nm or less. The lower limit of the median of the pore distribution is not particularly limited, but in reality, it is preferably 1 nm or more, and particularly preferably 3 nm or more. The pore shape may be a continuum of spherical or approximately elliptical pores, or a tubular shape.
[0033] The shape of the porous glass carrier can be appropriately selected depending on the purpose of use, for example, powder, granules, pellets, plates, blocks, fibers, nets, beads, honeycombs, etc.
[0034] <Gold fine particles> The gold fine particles are preferably gold nanoparticles or gold clusters. More specifically, the average particle size of the gold fine particles is preferably 10 nm or less, 9 nm or less, and particularly 8 nm or less. Gold fine particles having such an average particle size have high catalytic activity. The lower limit of the average particle size of the gold fine particles is not particularly limited, but may be, for example, 0.1 nm or more, particularly 0.2 nm or more. The average particle size means the diameter in the case of spherical particles, and the average major axis in the case of elliptical particles, and can be determined, for example, by creating a particle size distribution from transmission electron microscope (TEM) observation.
[0035] The amount of gold particles supported on the surface of the porous glass carrier is preferably 0.001 to 10% by weight, particularly 0.01 to 5% by weight. If the amount supported is too small, the catalytic activity decreases. If the amount supported is too large, no improvement in the catalytic activity can be expected. The amount of gold particles supported can be measured by eluting the supported gold particles from the carrier with aqua regia or the like, and subjecting the eluate to ICP emission spectrometry.
[0036] The catalyst of the present invention has the above-mentioned configuration, and therefore the catalytic activity of the porous glass carrier can be enhanced. Specifically, since the catalyst of the present invention exhibits CO oxidation catalytic activity, it can be particularly suitably used as a catalyst for purifying exhaust gas. The CO oxidation activity (CO conversion rate) means the ratio of CO lost by reaction to the amount of CO supplied, and can be measured, for example, by a flow-type fixed-bed type device. Specifically, the catalyst powder is packed into a sample tube and the tube is covered with silica wool. Next, pretreatment is performed at 250°C for 20 minutes using 20% O2 (Ar balance). 1% CO gas (in air) is used as the reaction gas and is supplied at a flow rate of 33 mL / min. The temperature is controlled by a thermostatic chamber, and the temperature is monitored by a platinum thermometer. The measurement temperature range can be 0 to 200°C. The CO concentration in the reaction gas is analyzed by a gas chromatograph (for example, GC-8A manufactured by Shimadzu Corporation), and the CO conversion rate can be calculated based on the CO concentration when the gas does not pass through the catalyst layer.
[0037] For example, the catalyst of the present invention preferably has a temperature at which the CO conversion rate reaches 50% (50% CO conversion temperature) of 200° C. or less, 180° C. or less, 150° C. or less, 130° C. or less, 100° C. or less, particularly preferably 90° C. or less. Because the 50% CO conversion temperature is low, the catalyst of the present invention can be used as a catalyst with excellent CO oxidation activity.
[0038] <Catalyst manufacturing method> The method for producing a catalyst of the present invention is characterized by comprising a solution preparation step of obtaining a gold complex solution by carrying out a hydrolysis reaction of the gold compound in a solution of pH 8 or more in which a halogen-free trivalent gold compound is dispersed, in the presence of a conjugate base of a weak acid, and a supporting step of impregnating a porous glass carrier with the gold complex solution and supporting gold particles on the porous glass carrier. In general, the gold compound used for producing a catalyst is often a compound containing a halogen (e.g., chloroauric acid). However, since the chlorine contained in chloroauric acid aggregates the gold particles, a separate processing step for removing the chlorine is required, which tends to make the process complicated. On the other hand, since the gold compound in the present invention is a halogen-free trivalent compound, the above problem does not occur and complicated processing steps are not required. Therefore, the catalyst can be easily produced.
[0039] Here, the conjugate base of a weak acid is A, which is represented by the following ionization formula of the weak acid HA. - The conjugate base of the weak acid is not particularly limited, but examples thereof include carboxylate anions such as acetate ion and propionate ion, carbonate ion, bicarbonate ion, citrate ion, phosphate ion, borate ion, and tartrate ion.
[0040] [ka]
[0041] As the trivalent compound not containing halogen, for example, the gold compounds shown in the following (1) to (4) can be suitably used. (1) Gold carboxylates: Au(CH3COO)3, Au(C2H5COO)3, etc. Basic salts such as Au(OH)(CH3COO)2, Au(OH)2(CH3COO) may also be included. (2) Gold oxide: Au2O3 (3) Gold hydroxide: Au(OH)3 (4) Double oxides of gold and alkali metals: NaAuO2, KAuO2, etc.
[0042] <Solution preparation process> First, a gold complex solution is prepared. Specifically, a gold complex solution is prepared by proceeding with a hydrolysis reaction of the gold compound in a solution of pH 8 or more in which a halogen-free trivalent gold compound is dispersed in the presence of a conjugate base of a weak acid. The solution (aqueous solution) of pH 8 or more in which the gold compound is dispersed may be prepared, for example, by dissolving a salt of a weak acid and a strong base in water in advance and adding a trivalent gold compound to the solution adjusted to a pH of 8 or more. Also, a salt of a weak acid and a strong base may be added to a solution in which a trivalent gold compound is dispersed in water to adjust the pH to 8 or more. In this case, the amount of salt added may be adjusted so that the pH of the solution is 8 or more. In addition, when gold acetate or the like is used as the gold compound, the gold compound itself generates acetate ions, which are the conjugate base of the weak acid, so that the pH may be adjusted using a strong base such as NaOH.
[0043] The pH of the solution in which the gold compound is dispersed is preferably 8 or higher, and more preferably 10 or higher. If the pH is less than 8, precipitation of gold hydroxide Au(OH)3 is likely to occur, making it difficult to obtain a uniform gold complex solution. There is no upper limit to the pH, but it is usually sufficient to set it to about 14 or lower. From the viewpoint of achieving uniform dispersion, the content of the gold compound in the solution is preferably about 0.001 to 10% by weight.
[0044] As a salt of a weak acid and a strong base, for example, an alkali metal ion (K + , Na + etc.), alkaline earth metal ions (Ca 2+ , B.A. 2+ It is preferable to use a salt of a weak acid that generates the above-mentioned conjugate base and contains an alkali metal ion as a cationic component.
[0045] In a solution having a pH of 8 or more in which the gold compound is dispersed, the gold compound completely dissolves as a gold hydroxo anion complex, thereby obtaining a transparent and uniform gold complex solution. More specifically, a transparent and uniform gold complex solution containing no halogen and in which the gold hydroxo anion complex is uniformly dissolved can be obtained. In this case, from the viewpoint of shortening the dissolution time, it is preferable to heat the solution having a pH of 8 or more in which the gold compound is dispersed to 80°C or higher, and it is particularly preferable to boil it under reflux. However, since the hydrolysis of the gold compound proceeds gradually, a transparent and uniform gold complex solution can be obtained over time even at room temperature.
[0046] For example, when gold acetate is used as the gold compound and sodium carbonate is used to adjust the pH, gold acetate can be added to deionized water and dispersed as a colloid using a touch mixer, ultrasonic cleaner, etc. When an aqueous sodium carbonate solution is added to this to adjust the pH to 8 or higher and boiled under reflux, the brown colloidal liquid changes into a yellow, transparent gold complex solution in a few minutes, and a colorless, transparent gold complex solution is obtained in about 10 minutes.
[0047] When gold hydroxide, gold oxide, or the like is used as the gold compound, it takes a longer time to obtain a transparent solution than when gold acetate is used, but regardless of the reaction conditions, a transparent gold complex solution can be obtained by reacting until there is no residual raw material powder or colloid left. Even if there is residual raw material powder left, the supernatant liquid may be separated off to obtain a transparent gold complex solution.
[0048] As described above, the gold complex solution used in the present invention does not contain halogen, which is a factor in the coarsening of gold nanoparticles and is a poisonous substance in catalytic reactions, and therefore a highly active catalyst with gold nanoparticles uniformly supported thereon can be easily obtained.
[0049] Here, the gold complex solution contains at least one ligand that is OH. - It is preferable that the catalyst contains a trivalent gold hydroxo anion complex having a planar tetragonal structure that does not contain a halogen anion as a ligand, a conjugate base of a weak acid that is not coordinated to gold, and a pH of 8 or more. Due to the presence of the conjugate base of the weak acid, the solution has a buffering effect and the pH is stable. This is thought to help the gold complex in the solution interact with the support under certain conditions, thereby generating uniform gold particles. In addition, since the solution does not contain a halogen, it is possible to prevent the gold particles from becoming coarse. Therefore, a highly active catalyst with gold particles uniformly supported can be easily obtained.
[0050] In the gold hydroxo anion complex solution, the trivalent gold hydroxo anion complex preferably satisfies, for example, the following conditions (1) to (4).
[0051] (1) It is a gold complex having a square planar structure represented by the following formula:
[0052] [ka]
[0053] (2) Gold is trivalent and is an anionic complex with an overall negative charge due to the coordination of anionic ligands a, b, c, and d. (3) At least one of the ligands a, b, c, and d is OH. - It is. (4) None of the ligands a, b, c, and d is a halogen anion. In the above-mentioned gold hydroxo anion complex, the OH ligands a, b, c, and d are - The ligand other than the cation may be any anion ligand other than a halogen anion. For example, acetate ion CH3COO - , Carbonate ion CO3 2- The following can be given as examples:
[0054] In the above formula, the value of n indicates the valence of the negative charge, which is determined by the type of anionic ligand. n is the total valence of the anionic ligands a, b, c, and d minus 3, which is the valence of gold.
[0055] Examples of the hydroxo anion complex of gold include the following compounds.
[0056] [ka]
[0057] The hydroxo anion complex of gold in each of the above formulas is [Au(OH)4] - , [Au(OH)2(CH3COO)2] - , [Au(OH)3(CO3)] 2- The impregnation solution may contain multiple types of gold complexes, and may contain only one type of gold complex. For example, the gold hydroxide anion complex may be [Au(OH)4] - and [Au(OH)3(CH3COO)] - The solution may be a solution containing
[0058] <Supporting process> Next, the gold complex solution prepared by the above method is impregnated into a porous glass carrier to support gold particles. More specifically, the gold complex solution is impregnated into a porous glass carrier, the water is removed to fix the gold complex on the carrier surface, and then a heat treatment is performed to produce gold particles.
[0059] (i) Impregnation into a porous glass carrier The method of impregnating the gold complex solution into the porous glass carrier is not particularly limited, and may be a method of immersing the carrier in a solution using an excess amount of the solution relative to the volume of the carrier, or may be impregnated by an incipient wetness method in which an amount of the solution corresponding to the pore volume of the carrier is dropped onto the carrier. In these cases, it is necessary to adjust the concentration of the gold complex solution in advance so as to obtain the desired loading amount. As described above, in the method for producing the complex of the present invention, the porous glass carrier contains SiO2 and ZrO2. Therefore, it is considered that the carrier has high alkali resistance, and the porous structure is not easily deteriorated even if the gold complex solution is a basic solution with a pH of 8 or more.
[0060] Next, the water is removed to immobilize the gold complex on the surface of the carrier. The method for removing the water is not particularly limited, and any method such as evaporation to dryness by heating on a hot plate, drying under reduced pressure with a rotary evaporator, or freeze-drying can be used.
[0061] The amount of gold particles fixed on the carrier surface may be any amount that provides the desired catalytic activity, and is preferably, for example, about 0.01 to 60% by weight based on the total amount of the gold particles and the porous glass carrier.
[0062] The specific surface area of the porous glass support carrying gold particles is, for example, 1 to 2000 m as measured by the BET method. 2 / g, especially 5 to 1000m 2 When the specific surface area has the above value, the number of active sites for catalytic reaction increases, and the mechanical strength is high.
[0063] (ii) Generation of gold particles by heat treatment After the gold complex is fixed on the surface of the porous glass carrier by the above-mentioned method, the gold particles can be supported by heating. The heating atmosphere is not particularly limited, and the heat treatment can be performed in various atmospheres such as an oxygen-containing atmosphere, a reducing atmosphere, an inert atmosphere, etc. For example, the oxygen-containing atmosphere can be an air atmosphere, or a mixed gas atmosphere in which oxygen is diluted with nitrogen, helium, argon, etc. For example, the reducing atmosphere can be about 1 to 10 volume % hydrogen gas diluted with nitrogen gas, carbon monoxide gas, etc. For example, the inert atmosphere can be nitrogen, helium, argon gas, etc.
[0064] The heat treatment temperature is equal to or lower than the heat resistance temperature of the porous glass carrier, and is usually about 100 to 600° C., and in order to obtain stable and fine gold particles, it is preferably about 200 to 400° C. The heat treatment time is not particularly limited, but after reaching a predetermined heat treatment temperature within the above-mentioned temperature range, heating should be continued for 5 minutes or more, and particularly 10 minutes or more.
[0065] (iii) Washing with water to remove soluble salts and drying Next, the porous glass carrier after the above-mentioned heat treatment is washed with water. In the porous glass carrier after the heat treatment, conjugate bases of weak acids such as acetate ions and carbonate ions remain in the form of alkali metal salts, alkaline earth metal salts, etc. If these salts remain on the surface, they may physically block active sites and cause a decrease in activity, so it is preferable to remove these salts by washing with water until the washing liquid becomes neutral.
[0066] The washing method is not particularly limited, and any general washing method can be appropriately applied, such as a method of washing by pouring deionized water onto filter paper using a suction filter, a decantation method in which the support powder and deionized water are placed in a beaker and washed while replacing the supernatant, or a washing method using a centrifuge to separate the precipitate and water.
[0067] After washing with water, the catalyst in which gold particles are supported on the porous glass carrier can be obtained by drying. The drying temperature may be any temperature lower than the temperature at which gold particles are generated by heat treatment, and is usually between room temperature and 150°C.
[0068] The above-mentioned method can obtain a gold microparticle catalyst in which gold microparticles are uniformly supported on a porous glass carrier. The gold microparticle catalyst obtained by the method of the present invention does not contain halogens that are poisonous to catalytic reactions, and therefore exhibits high activity in various catalytic reactions. For example, it can be suitably used for indoor air purification such as carbon monoxide oxidation removal. It can also be used in various fields in which gold microparticle catalysts have been used in the past, such as air environment conservation such as NOx reduction, fuel cell-related reactions such as selective oxidation of carbon monoxide in hydrogen, and chemical process reactions such as propylene oxide synthesis reaction from propylene.
[0069] <Production of Porous Glass Carrier> The porous glass carrier used in the present invention is preferably produced by dissolving one phase of the spinodally separated glass with an acid. More specifically, the method for producing the porous glass carrier preferably includes, for example, a phase separation step of heat-treating a glass base material to separate it into two phases to obtain a phase-separated glass material, and a removal step of removing one phase of the phase-separated glass material with an acid.
[0070] <Phase separation process> In the phase separation step, the glass base material is heat-treated to separate into two phases to obtain a phase-separated glass material. The glass base material preferably contains, for example, in mole percent, 40-80% SiO2, more than 0-40% B2O3, more than 0-20% Na2O, 0-20% K2O, 0-10% TiO2, more than 20% ZrO2, 0-10% Al2O3, and 0-20% RO (R is at least one selected from Mg, Ca, Sr, and Ba). The reason for specifying the content of each component in the glass base material as above will be explained below. Unless otherwise specified, in the explanation of the component content of the glass base material, "%" means "mol%".
[0071] SiO2 is a component that forms a glass network. The SiO2 content is preferably 40 to 80%, 45 to 75%, 47 to 60%, and particularly preferably 50 to 65%. If the SiO2 content is too low, the glass base material is likely to break during the manufacturing process. If the SiO2 content is too high, phase separation becomes difficult.
[0072] B2O3 is a component that forms a glass network and promotes phase separation. The content of B2O3 is preferably more than 0 to 40%, 10 to 30%, and particularly preferably 15 to 25%. If the content of B2O3 is too low, phase separation is difficult to proceed. If the content of B2O3 is too high, the weather resistance of the glass base material is likely to decrease.
[0073] Na2O is a component that lowers the melting temperature to improve meltability, and also promotes phase separation. The Na2O content is preferably more than 0 to 20%, 3 to 15%, and particularly preferably 4 to 10%. If the Na2O content is too low, it is difficult to obtain the above effects. If the Na2O content is too high, phase separation becomes difficult to proceed.
[0074] K2O is a component that lowers the melting temperature of glass to improve meltability, and also promotes phase separation. It is also a component that increases the ZrO2 content in the silica-rich phase. Therefore, by including K2O, the ZrO2 content in the obtained porous glass carrier increases, and the alkali resistance can be improved. The content of K2O is preferably 0 to 20%, more than 0.3 to 5%, 0.5 to 5%, and particularly preferably 0.8 to 3%. If the content of K2O is too low, it is difficult to obtain the above effect. On the other hand, if the content of K2O is too high, phase separation becomes difficult.
[0075] The content of Na2O+K2O (total amount of Na2O and K2O) is preferably more than 0 to 20%, 2 to 15%, 4 to 12%, and particularly preferably 5 to 10%. If the content of Na2O+K2O is too small, the melting temperature may become high and the melting property may decrease. In addition, phase separation becomes difficult. If the content of Na2O+K2O is too large, phase separation becomes difficult.
[0076] TiO2 is a component that increases the etching rate during acid treatment of the glass base material. The TiO2 content is preferably 0 to 10%, 0.1 to 58%, and particularly preferably 0.5 to 56%. If the TiO2 content is too low, it becomes difficult to obtain the above effects. On the other hand, if the TiO2 content is too high, the porous glass carrier becomes colored and the visible light transmittance is easily reduced.
[0077] ZrO2 is a component that improves the weather resistance of the glass base material and the alkali resistance of the porous glass carrier. The content of ZrO2 is preferably more than 0 to 20%, 2 to 15%, and particularly preferably 2.5 to 12%. If the content of ZrO2 is too low, it is difficult to obtain the above effects. On the other hand, if the content of ZrO2 is too high, devitrification is likely to occur and phase separation is difficult to occur.
[0078] The content of TiO2+ZrO2 (total amount of TiO2 and ZrO2) is preferably more than 0 to 25%, 1 to 20%, and particularly preferably 3 to 20%. If TiO2+ZrO2 is too small, the alkali resistance of the porous glass carrier is likely to decrease. On the other hand, if TiO2+ZrO2 is too large, phase separation becomes difficult.
[0079] Al2O3 is a component that improves the weather resistance and mechanical strength of the porous glass carrier. The content of Al2O3 is preferably 0 to 10%, 0.1 to 7%, and particularly preferably 1 to 5%. If the content of Al2O3 is too high, the melting temperature increases and the melting property tends to decrease.
[0080] MgO, CaO, SrO and BaO are components that increase the ZrO2 content in the silica-rich phase. Therefore, by including RO, the ZrO2 content in the resulting porous glass carrier increases, and the alkali resistance can be improved. The above components are also components that improve the weather resistance of the porous glass carrier. MgO+CaO+SrO+BaO (the total amount of MgO, CaO, SrO and BaO) is preferably 0-20%, 1-17%, 3-15%, 4-13%, 5-12%, and particularly preferably 6.5-12%. If these contents are too high, phase separation becomes difficult. The contents of MgO, CaO, SrO and BaO are preferably 0-20%, 1-17%, 3-15%, 4-13%, 5-12%, and particularly preferably 6.5-12%, respectively. When at least two components selected from MgO, CaO, SrO and BaO are contained, the total amount is preferably 0 to 20%, 1 to 17%, 3 to 15%, 4 to 13%, 5 to 12%, particularly preferably 6.5 to 12%. It is preferable to use CaO, since it has a particularly large effect of improving the alkali resistance of the porous glass carrier.
[0081] The glass base material may contain the following components in addition to the above components.
[0082] ZnO is a component that increases the ZrO2 content in the silica-rich phase. The ZnO content is preferably 0 to 20%, 0 to 10%, and particularly preferably 0 to less than 3%. If the ZnO content is too high, phase separation becomes difficult.
[0083] P2O5 is a component that promotes phase separation. The content of P2O5 is preferably 0 to 10%, more preferably 0.01 to 5%, and even more preferably 0.05 to 2%. If the content of P2O5 is too high, crystallization may occur.
[0084] Furthermore, Li2O, La2O3, Ta2O5, TeO2, Nb2O5, Gd2O3, Y2O3, Eu2O3, Sb2O3, SnO2, Bi2O3, etc. may be contained in an amount of 15% or less, 10% or less, particularly 5% or less, with a total amount of 30% or less.
[0085] In addition, since PbO is an environmentally hazardous substance, it is preferable that it is not substantially contained.
[0086] A glass batch prepared to obtain a desired glass composition is melted, for example, at 1300 to 1600° C. for 3 to 12 hours. The molten glass is then molded and slowly cooled, for example, at 400 to 600° C. for 10 minutes to 10 hours to obtain a glass base material. The shape of the obtained glass base material is not particularly limited and can be appropriately selected depending on the shape of the required porous glass carrier.
[0087] Next, the obtained glass base material is heat-treated to separate into two phases, a silica-rich phase and a boron oxide-rich phase (spinodal phase separation), to obtain a phase-separated glass material. The heat treatment temperature of the glass base material is preferably 500 to 800°C, 600 to 780°C, and particularly 650 to 750°C. If the heat treatment temperature is too high, the glass base material may soften and deform. If the heat treatment temperature is too low, it is difficult to separate the phases of the glass base material. The heat treatment time is preferably 1 minute or more, 10 minutes or more, and particularly 30 minutes or more. If the heat treatment time is too short, it is difficult to separate the phases of the glass base material. There is no particular limit to the upper limit of the heat treatment time, but since phase separation does not proceed beyond a certain level even if the heat treatment is performed for a long period of time, it is practically 180 hours or less.
[0088] In the phase separation process, a silica-containing layer (a layer containing approximately 80 mol% or more of silica) may be formed on the outermost surface of the phase-separated glass material. Since the silica-containing layer is difficult to remove with acid, when the silica-containing layer is formed, the phase-separated glass material is cut or polished, the silica-containing layer is removed, and then the material is immersed in acid, which makes it easier to remove the boron oxide-rich phase. In addition, the phase-separated glass material may be immersed in hydrofluoric acid for a short time to remove the silica-containing layer.
[0089] <Removal process> Next, the phase-separated glass material is immersed in an acid solution to remove the boron oxide-rich phase, thereby obtaining a porous glass carrier. As the acid solution, hydrochloric acid or nitric acid is preferably used, and these acid solutions may be used in combination. The concentration of the acid solution is preferably 0.1 to 5 mol / L, particularly preferably 0.5 to 3 mol / L. The immersion time in the acid solution is preferably 0.1 hours or more, 0.2 hours or more, particularly preferably 1 hour or more. If the immersion time is too short, etching becomes insufficient, making it difficult to obtain a porous glass carrier having a desired pore size, pore volume, or specific surface area. If the immersion time is too long, the porous glass carrier may dissolve in the acid solution, so the upper limit of the immersion time is preferably 50 hours or less, 40 hours or less, 30 hours or less, 20 hours or less, particularly preferably 10 hours or less. The immersion temperature is preferably 20°C or more, 25°C or more, particularly preferably 30°C or more. If the immersion temperature is too low, etching becomes insufficient, making it difficult to obtain a porous glass carrier having a desired continuous pores. The upper limit of the immersion temperature is not particularly limited, but in practice it is 99° C. or lower.
[0090] In addition, in the porous glass carrier from which the boron oxide-rich phase has been removed with an acid, SiO2 gel and ZrO2 gel derived from the boron-rich phase remain in the pores. Therefore, in addition to the removal of the boron oxide-rich layer, it is preferable to remove the ZrO2 gel and SiO2 gel by additional etching with an acid solution and an alkaline solution.
[0091] The ZrO2 gel can be removed, for example, by immersing the porous glass carrier in sulfuric acid. The concentration of sulfuric acid is preferably 0.1 to 5 mol / L, particularly preferably 1 to 5 mol / L. The immersion time in sulfuric acid is preferably 0.1 hours or more, 0.2 hours or more, particularly preferably 1 hour or more. If the immersion time is too short, it becomes difficult to remove the ZrO2 gel. There is no particular upper limit to the immersion time, but it is practically 50 hours or less, 40 hours or less, 30 hours or less, 20 hours or less, or even 10 hours or less. The immersion temperature is preferably 20°C or more, 25°C or more, particularly preferably 30°C or more. If the immersion temperature is too low, it becomes difficult to remove the ZrO2 gel. There is no particular upper limit to the immersion temperature, but it is practically 99°C or less.
[0092] The SiO2 gel can be removed, for example, by immersing the porous glass carrier in an alkaline solution. As the alkaline solution, an aqueous sodium hydroxide solution, an aqueous potassium hydroxide solution, or the like can be used. These alkaline solutions may be mixed and used. The concentration of the alkaline solution is preferably 0.1 to 5 mol / L, particularly 0.5 to 3 mol / L. The immersion time in the alkaline solution is preferably 0.1 hours or more, particularly 0.2 hours or more. If the immersion time is too short, it becomes difficult to remove the SiO2 gel. There is no particular limit to the upper limit of the immersion time, but it is practically 20 hours or less, and further 10 hours or less. The immersion temperature is preferably 15°C or more, particularly 20°C or more. If the immersion temperature is too low, it becomes difficult to remove the SiO2 gel. There is no particular limit to the upper limit of the immersion temperature, but it is practically 99°C or less. EXAMPLES
[0093] The present invention will be described below based on examples, but the present invention is not limited to these examples.
[0094] [Table 1]
[0095] [Table 2]
[0096] [Table 3]
[0097] <Example> First, the raw materials were mixed to obtain the glass composition shown in Table 1. Next, the mixed raw materials were placed in a platinum crucible and melted at 1500°C for 4 hours. During melting, the mixture was stirred using a platinum stirrer to homogenize the molten glass. Next, the obtained molten glass was poured onto a metal plate and formed into a plate shape, and then slowly cooled at 540°C to 580°C for 30 minutes to obtain a glass base material. The obtained glass base material was cut and polished to a size of 10 mm x 10 mm x 0.5 mm.
[0098] Next, the glass preform was heat-treated to obtain a phase-separated glass material. Specifically, the glass preform was placed in an electric furnace and heat-treated at 695° C. for 24 hours.
[0099] The obtained phase-separated glass material was subjected to the following treatments. First, it was immersed in 1 mol / L nitric acid (95°C) for 48 hours, and then washed with ion-exchanged water. Next, as a second acid treatment, it was immersed in 3 mol / L sulfuric acid (95°C) for 48 hours, and then washed with ion-exchanged water. Next, it was immersed in 0.5 mol / L aqueous sodium hydroxide solution (25°C) for 5 hours, and then washed with ion-exchanged water. Finally, the water was evaporated by natural drying to obtain a porous glass carrier.
[0100] When the cross sections of the obtained porous glass carriers were observed with a FE-SEM (field emission scanning electron microscope, Hitachi SU-8220), all glasses had a skeleton structure based on spinodal phase separation. The compositions and median pore size distributions of the obtained porous glass carriers are shown in Table 2. The compositions of the porous glass carriers were investigated with an EDX (energy dispersive X-ray analyzer, Horiba EMAX Evolution EX-370 X-Max150). The median pore size distribution was measured with a pore size distribution measuring device (Anton Paar QUADRASORB SI).
[0101] Next, gold particles were supported on the porous glass support. First, 95.2 mg of gold acetate Au(CH3COO)3 (Thermo Scientific) was added to 50 mL of 0.1 mol / L sodium carbonate aqueous solution, and then ultrasonically dispersed and boiled under reflux for 90 minutes. This operation produced [Au(OH)4] - A gold complex solution containing the above was obtained. Next, an amount of the gold complex solution corresponding to the amount of gold to be supported was measured and added to 1 g of a granular porous glass carrier, and evaporated to dryness at 40°C. After heat treatment at 350°C for 30 minutes in an air atmosphere, the carrier was washed with water until the washing liquid became neutral, and dried at 100°C to obtain a gold-supported porous glass carrier. When observed with FE-SEM, gold fine particles with an average particle size of 6 nm were supported in all of Examples 1 to 3. The average particle size of the gold fine particles was determined by creating a particle size distribution from transmission electron microscope (TEM) observation.
[0102] The CO oxidation activity (CO conversion rate) was measured using a flow-type fixed-bed apparatus. First, 100 mg of catalyst powder was packed into a sample tube and covered with silica wool. Pretreatment was performed at 250°C for 20 minutes using 20% O2 (Ar balance). 1% CO gas (in air) was used as the reaction gas and was supplied at a flow rate of 33 mL / min. The temperature was controlled by a thermostatic bath and monitored with a platinum thermometer. The measurement temperature range was 0 to 200°C. The CO concentration in the reaction gas was analyzed by a gas chromatograph (Shimadzu GC-8A), and the CO conversion rate was calculated based on the CO concentration when not passing through the catalyst layer. The 50% CO conversion temperature is shown in Table 3.
[0103] <Comparative Example> Dimethylgold(III), gold(II) acetylacetonate and SiO2 powder were pulverized in an argon gas atmosphere and then calcined in air at 300°C to prepare gold-supported SiO2 (Comparative Example 1). The 50% CO conversion temperature of Comparative Example 1 was evaluated in the same manner as in the Examples. The evaluation results are shown in Table 3.
[0104] As shown in Table 3, the 50% CO conversion temperature in Examples 1 to 3 was low, at 80°C or lower, while the 50% CO conversion temperature in Comparative Example 1 was high, at over 200°C. [Industrial Applicability]
[0105] According to the present invention, a catalyst made of a porous glass support on which gold particles are uniformly supported can be obtained. The catalyst does not contain halogens that are poisonous to catalytic reactions and can be obtained by a simple processing method. In addition, the catalyst of the present invention has high CO oxidation activity, making it suitable as a catalyst for purifying exhaust gas.
Claims
1. SiO 2 and ZrO 2 A catalyst comprising gold particles supported on a porous glass support comprising:
2. The porous glass carrier further comprises TiO 2 The catalyst of claim 1 comprising:
3. 3. The catalyst according to claim 1, wherein the median pore size distribution of the porous glass support is 1 to 1000 nm.
4. 3. The catalyst according to claim 1, wherein the average particle size of the gold particles is 0.1 to 10 nm.
5. The catalyst according to claim 1 or 2, which is an exhaust gas purification catalyst.
6. A method for producing the catalyst according to claim 1 or 2, comprising the steps of: a solution preparation step of carrying out a hydrolysis reaction of the gold compound in the presence of a conjugate base of a weak acid in a solution having a pH of 8 or more in which a halogen-free trivalent gold compound is dispersed to obtain a gold complex solution; The method for producing a catalyst includes a supporting step of impregnating the porous glass support with the gold complex solution to cause the porous glass support to support gold fine particles.
7. The method for producing a catalyst according to claim 6, wherein the porous glass support is produced by dissolving one phase of spinodally separated glass with an acid.
Citation Information
Patent Citations
Method for dispersing and fixing gold fine particle to carrier, gold fine particle-deposited carrier obtained thereby, catalyst and colorant
JP2008259993A
Cited By
Packaging machine and systems
US12291365B2